2012
DOI: 10.5543/tkda.2012.59144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long Term Clinical Outcomes, Event Free Survival Rates of Patients Undergoing Enhanced External Counterpulsation (EECP) for Coronary Artery Disease in the United States and Turkey

Abstract: Patients presenting for EECP treatment from TR had different baseline profiles from US patients. However, despite the high risk baseline characteristics, both cohorts achieved similar reduction in angina. In the long term follow-up, the MACE rate was low and the improvement after EECP was sustained in most of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Moreover, the possible explanations and conclusions need further studies to verify. Previous studies 28 , 33 , 37 showed that about more than 70% of the patients retainted improvement in CCS after 1-year follow-up. Erdling et al 32 and Michaels et al 7 reported a reduction by ≧1 angina class that sustained at 2 years.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the possible explanations and conclusions need further studies to verify. Previous studies 28 , 33 , 37 showed that about more than 70% of the patients retainted improvement in CCS after 1-year follow-up. Erdling et al 32 and Michaels et al 7 reported a reduction by ≧1 angina class that sustained at 2 years.…”
Section: Discussionmentioning
confidence: 90%
“…The follow-up period varied from 1 to 42 months. The patient population were male predominately, and baseline CCS were I–IV, II–IV, and III–IV correspond to the 4, 20 , 21 , 33 , 34 8, 24 26 , 28 , 29 , 32 , 35 , 37 and 3 studies, 23 , 30 , 31 respectively. The remaining studies on CCS were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that EECP therapy was effective in relieving symptoms in patients with refractory angina and may reduce inducible ischaemia at dobutamine stress echocardiography, especially in patients with reduced systolic function and compromised segmental kinesis. (Novo et al, 2006) Although randomized (including placebo-controlled) and nonrandomized studies have shown beneficial effects of EECP therapy, investigators saw the need to assess EECP's effectiveness in real-world settings, leading them to develop the International EECP Patient Registry (IEPR) under the management of the University of Pittsburgh (Michaels et al 2004, Soran et al, 2010. More than 5000 patients were enrolled in phase I and another 2500 patients enrolled in phase II of the study, and more than 90 centers participated.…”
Section: Eecp Therapy In Cad Managementmentioning
confidence: 99%
“…However, both cohorts achieved substantial reduction in angina with high event free survival rates at 6 months. (Soran et al, 2010) EECP was suggested as a safe treatment option for selected symptomatic PCI candidates with obstructive CAD. Baseline characteristics and 1-year outcome in 2 cohorts of PCI candidates presenting with stable symptoms: 323 patients treated with EECP in the IEPR, and 448 NHLBI Dynamic Registry patients treated with elective PCI, were compared.…”
Section: Eecp Therapy In Cad Managementmentioning
confidence: 99%
“…Coronary artery disease (CAD) is a leading cause of death and disability worldwide. An estimated 17.6 million patients in the United States suffer from symptomatic CAD and despite optimal medical therapy, such as medications, percutaneous coronary intervention, and cardiac bypass surgery, there are an estimated up to 900,000 patients who suffer from disabling angina [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%